Bovine PMN responses to extracellular vesicles released by Besnoitia besnoiti tachyzoites and B. besnoiti-infected host cells - Espinosa, Gabriel; Salinas-Varas, Constanza; Rojas-Barón, Lisbeth; Preußer, Christian; Pogge von Strandmann, Elke; Gärtner, Ulrich; Conejeros, Iván; Hermosilla, Carlos; Taubert, Anja; Justus Liebig University Giessen (My University, 2024)
Bovine besnoitiosis is a re-emerging cattle disease caused by the apicomplexan parasite Besnoitia besnoiti, which severely affects individual animal welfare and profitability in cattle industry. We recently showed that B. besnoiti tachyzoite exposure to bovine polymorphonuclear neutrophils (PMN) effectively triggers neutrophil extracellular trap (NET) formation, leading to parasite immobilization hampering host cell infection. So far, the triggers of this defense mechanism remain unclear. Emerging evidence indicates that extracellular vesicles (EVs) modulate PMN effector functions, such as ROS production or NET formation. Therefore, we tested whether exposure of bovine PMN to EVs from different cellular sources affects classical PMN effector functions and cytokine/chemokine secretion. EVs were isolated from B. besnoiti-infected and non-infected host cells (bovine umbilical vein endothelial cells, BUVEC), from tachyzoite-exposed bovine PMN and from B. besnoiti tachyzoites. EV concentration and size was determined by Nano-Flow cytometry and EV nature was confirmed by both classical EV markers (CD9 and CD81) and transmission electron microscopy (TEM). Overall, PMN stimulation with both BUVEC- and tachyzoite-derived EVs significantly induced extracellular DNA release while EVs from PMN failed to affect NET formation. BUVEC and tachyzoite EV-driven NET formation was confirmed microscopically by the presence of DNA decorated with neutrophil elastase (NE) and histones in typical NET structures. Moreover, confocal microscopy revealed EVs to be internalized by bovine PMN. Referring to PMN activation, EVs from the different cellular sources all failed to affect glycolytic or oxidative responses of bovine PMN as detected by Seahorse®-based analytics and luminol-based chemoluminescence, thereby denying any role of NADPH oxidase (NOX) activity in EV-driven NET formation. Finally, exposure to B. besnoiti-infected BUVEC-derived EVs induced IL-1β and IL-6 release, but failed to drive CXCL8 release of bovine PMN. Hence, we overall demonstrated that EVs of selected cellular origin owned the capacity to trigger NOX-independent NET formation, were incorporated by PMN and selectively fostered IL-1β and IL-6 release.
Keywords: ddc:630